ANALYSIS OF AFTERSHOCK SEISMICITY (М ≥ 4.0) OF THE VAN EARTHQUAKE OF 23.10.2011 (M = 7.2) FOR THE PERIOD 23.10.2011– 30.11.2012 (Proceedings of the YSU C: Geological and Geographical Sciences, 2021)
The Armenian Highlands are characterized by the presence of sources of strong earthquakes, which also affect the level of seismic hazard in the territory of Armenia. In particular, the Van earthquake (23.10.2011, M = 7,2) manifested itself in many areas by intense seismic vibrations. Therefore, a comprehensive analysis of the active phase (23.10.2011–30.11.2012) of the aftershock process of this earthquake from the point of view of its possible impact on the seismic geodynamics of other potentially dangerous zones of the region under study is very important. The study of the spatio-temporal distribution of aftershocks with a magnitude of M ≥ 4,0 made it possible, in particular, to identify a certain relationship between seismic-geodynamic processes of some tectonic structures and focal zones of the Armenian Highlands.
Keywords: aftershock seismicity; seismic focal zone; seismogeodynamics; spatio-temporal distribution of earthquake epicenters; Armenian highlands; seismological data; tectonic structure; main seismic shock